EFFECT OF DIFFERENT CONDITIONS OF WELSH ONION SEED STORAGE ON GERMINATION AND CYTOGENETIC CHARACTERISTICS OF THEIR SEEDLINGS - I. A. Prokopiev; G. V. Filippova; A. A. Shein (Вавиловский журнал генетики и селекции)
By the example of fast-ageing Allium fistulosum seeds, it is shown that the storage temperature of +4, –6 and –18 °C, regardless of the used gas atmosphere does not affect laboratory germination, mitotic activity, or the frequency of chromosome aberrations and lags in the apical meristem of seedling roots in comparison to the control. The conditions best for seed storage are: +4 °C (argon, carbon dioxide), –6 °C (air, argon, nitrogen, carbon dioxide) and –18 °C (air), as proven by the lowest frequency of micronuclei in root cells of seedlings.